2013
DOI: 10.1080/07391102.2013.770374
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of a flocculent protein fromMoringa oleifera: experimental evidence andin silicointerpretation

Abstract: Many proteins exist in dimeric and other oligomeric forms to gain stability and functional advantages. In this study, the dimerization property of a coagulant protein (MO2.1) from Moringa oleifera seeds was addressed through laboratory experiments, protein-protein docking studies and binding free energy calculations. The structure of MO2.1 was predicted by homology modelling, while binding free energy and residues-distance profile analyses provided insight into the energetics and structural factors for dimer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The nonpolar contribution to the desolvation free energy is computed using the solvent accessible surface area. The polar contribution is computed using either generalised Born approach (in GB approach) or Poisson Boltzmann approach (as in PB approach)434445. Overall, these two approaches differ with respect to the polar term in the desolvation free energy.…”
Section: Resultsmentioning
confidence: 99%
“…The nonpolar contribution to the desolvation free energy is computed using the solvent accessible surface area. The polar contribution is computed using either generalised Born approach (in GB approach) or Poisson Boltzmann approach (as in PB approach)434445. Overall, these two approaches differ with respect to the polar term in the desolvation free energy.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, both the hemagglutinin MoL and the flocculating lectin cMoL presented molecular profiles similar to Mo -CBP 2 , appearing in dimer or trimer conformations (Katre et al, 2008; Luz et al, 2013). The in silico analysis of the recombinant protein MO 2.1 showed that the dimer form was the most stable structural arrangement (Pavankumar et al, 2014). Thus, it is plausible to suggest that the M. oleifera proteins aggregate into oligomers to attain a stable and lower energy structural state.…”
Section: Discussionmentioning
confidence: 99%
“…Crude seed extract (MOCE) was prepared by grinding the seeds followed by solvent treatments as detailed in Ghebremicahel et al The purified fractions (1 µg µL −1 ) of MOCP and MOCRP were obtained from our earlier study . All three protein fractions (MOCE, MOCP and MOCRP) were resolved on 10% SDS‐PAGE stained with Coomassie Brilliant Blue‐R250.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular docking studies were performed using the homology‐modeled structure of MOCP, recently reported by us, which was docked to establish a stable complex with congo red, tartrazine and DDT to analyze their affinity and molecular interactions. The standardized parameters of the molecular docking tool, AutoDock 4.2 was used to compute the molecular interactions between the protein and ligands (pollutants).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation